The process of fledging in the Mountain Bluebird. Issue 4 (December 2013) - Johnson, L. Scott; Hebert, Rachel M.; Napolillo, Felicia M.; Allen, Allison
ABSTRACT Fledging is a critical event in the avian breeding cycle, but remains unstudied in almost all species. As a result, little is known about factors that cause nestlings to leave nests. We documented fledging behavior in a box‐nesting population of Mountain Bluebirds (Sialia currucoides) using radio‐frequency identification. We attached a passive integrated transponder (PIT tag) to the leg of each nestling in 40 nests. An antenna checked for the presence of a transponder signal (i.e., a nestling) at nest‐box entrances every 2 s. The time of last detection of a nestling was taken as the time that nestling fledged. We found that fledging began when the oldest nestlings were 15–22 d old. Broods that were ahead in development, as measured by primary feather length, fledged at relatively younger ages. All nestlings fledged on the same day at 33 nests (83%) and over 2 d at remaining nests. When all nestlings fledged on the same day, fledging usually began in the morning and median time between the first and last fledging was 55 min (range = 2.3 min–10.6 h). When young fledged over 2 d, fledging always began >8 h after sunrise and usually just one nestling fledged the first day, suggesting that this fledging may have been accidental. Clutches in our population often hatch asynchronously, which sets up a hierarchy within broods in developmental state, size, and competitive ability. In such situations, fledging may be initiated by one of the most‐developed and hence most‐competitive nestlings in a brood, presumably when it reaches a certain threshold state of development. Alternatively, fledging may begin when a less‐developed, less‐competitive, and probably hungrier nestling leaves the nest, presumably to gain better access to food. We used the proportion of time that a nestling was able to occupy the nest‐box entrance late in the nestling stage, waiting to intercept parents with food, as an index of nestling competitive ability. Assuming that the number of nest entrance detections reliably indicates nestling competitive ability, we found that the most‐competitive nestling fledged first at over half of all nests, supporting the notion that fledging usually begins when oldest nestlings reach a threshold state of development.